Response mechanisms to joint exposure of triclosan and its chlorinated derivatives on zebrafish (Danio rerio) behavior. (February 2018) - Liu, Jinfeng; Sun, Limei; Zhang, Hongqin; Shi, Mengru; Dahlgren, Randy A.; Wang, Xuedong; Wang, Huili
Abstract: Triclosan (TCS), 2, 4, 6-trichlorophenol (2, 4, 6-TCP) and 2, 4-dichlorophenol (2, 4-DCP) frequently co-exist in real-world aquatic environments; the latter two contaminants contributing to TCS photolytic products or chlorinated derivatives. There is a paucity of information regarding their joint toxicity to aquatic organisms leading us to study their effects on the swimming behavior of zebrafish ( Danio rerio ). Herein, we reported that 0.28 mg/L TDT exposure (mixtures of TCS, 2, 4, 6-TCP and 2, 4-DCP) enhanced 24-hpf embryonic spontaneous movement frequency, 96-hpf larval activity; however, the 0.56 and 1.12 mg/L TDT treatments decreased all of these behavioral endpoints. All adult behavioral tests demonstrated that chronic TDT exposure (0.14 mg/L) led to hyperactivity and restlessness in adult zebrafish. A 0.14 mg/L TD DATE /@ "M/d/yyyy" 11/21/2017T treatment led to anxiety-like behavior in a bottom dwelling test and excessive panic and low hedging capacity in a conditioned place preference test. Social interaction test demonstrated that zebrafish preferred quiet and isolated space in response to TDT stress. Zebrafish memory was significantly decreased in a T-maze experiment. Whole mount in situ hybridization of pax2a and bcl2l11 genes revealed that their differential expression in the brain and skeleton were related to the corresponding phenotypic behavioral abnormality. A series of biomarker and estrogen receptor assays demonstrated that TDT acute exposure caused abnormal energy metabolism and neurological diseases. AO staining revealed that TDT exposure produced vascular ablation in the head, as well as the occurrence of massive apoptosis in the brain. TEM observation showed pyknosis of nucleus following TDT exposure. These results allow assessment of mechanisms for zebrafish abnormal behavior in response to TDT exposure, and are useful for early intervention and gene therapy of contaminant-induced diseases. Highlights: Joint toxicity of triclosan and its main products (TDTs) to zebrafish behavior. TDTs-stress produced larval abnormality and adult anxiety- or autism-like behavior. Behavioral effects focus on social interaction, preference, T-maze tests and so on. Abnormal behavior from changes in the related gene, biomarker and pathological tissue. TDTs produced vascular ablation in head and occurrence of massive apoptosis in brain.